Adele Goodwin: capstone - Goodwin, Adele, artist (Colorado State University. Libraries, 2026)
The artist's statement: Hi! I am a cross-disciplinary graphic designer and creative leader with experience in brand design, event coordination, client communication, and digital media production. Skilled in Adobe Creative Cloud, creative project management, cross-team collaboration, and delivering polished visual solutions on deadline. Professional background includes campus marketing, student media leadership, museum and attraction operations, fabrication lab assistance, and public-facing customer service. Strong ability to ideate, design, and execute across print and digital collateral, large-scale publications, and event branding.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design